VD_FINDINFO HC / 2011 / 293 vom 13. April 2011 - VD Tribunal cantonal (2011)
EXÉCUTION DE L'OBLIGATION, EXCEPTION D'INEXÉCUTION | 82 CO, 444 CPC, 445 CPC, 451 ch. 2 CPC, 452 al. 1ter CPC, 465 al. 1 CPC